2021
DOI: 10.2147/ijwh.s309299
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Leptin During Menstrual Cycle and Its Relation to the Hypothalamic–Pituitary–Gonadal (HPG) Axis: A Systematic Review

Abstract: Recently, adipose tissue has been identified as endocrine organ in addition to its action as energy store; it produces a large number of biologically active mediators known as adipocytokines. Significantly, adipocytokines were found to be involved in the physiology of many body functions, including reproduction. The role of body weight, body fat compositions, and nutrition has been largely investigated using animal models and human studies. Malnutrition and/or abnormal body weight may induce disturbances in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
(181 reference statements)
0
14
0
4
Order By: Relevance
“…This concentration difference between the three groups is due to the positive effect of high estrogen in female pregnant women compared to male pregnant women [45]. Several studies indicated the positive effect of leptin on estrogen in female pregnant women when it recorded a high level of this hormone compared to male pregnant women [46]. The positive relationship between cortisone and Testosterone was the reason for the superiority of testosterone in male pregnant women in all groups.…”
Section: Discussionmentioning
confidence: 88%
“…This concentration difference between the three groups is due to the positive effect of high estrogen in female pregnant women compared to male pregnant women [45]. Several studies indicated the positive effect of leptin on estrogen in female pregnant women when it recorded a high level of this hormone compared to male pregnant women [46]. The positive relationship between cortisone and Testosterone was the reason for the superiority of testosterone in male pregnant women in all groups.…”
Section: Discussionmentioning
confidence: 88%
“…Leptin and irisin are thought to play a role in the connection between body fat storage and the hypothalamic-pituitary-gonad (HPG). Leptin controls the normal physiology of the reproductive system and interacts with the HPG axis through a complex mechanism that links energy homeostasis to reproduction (16), while irisin stimulates gonadotropin gene expression in pituitary cells (57). This may indicate that the relationship between leptin, irisin, and sex hormones is governed by a complex feedback loop, rather than a simple one-way relationship.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to weight loss by influencing food intake and increasing energy expenditure, and is thought to control food intake at least in part through neuropeptide Y (NPY). Leptin is not only a molecule that reflects energy storage in the body, but is also an important cytokine involved in many physiological functions, such as the inflammatory response, insulin sensitivity, bone metabolism, immunity, and, most importantly, reproductive function (16). High leptin levels are an important manifestation of obesity, and children and adolescents show increased leptin levels with increasing body fat mass (17).…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was determined based on previous studies that investigated the cyclical changes of different hormones during the menstrual cycle, where the number of participants ranged from 8 to 259. 7 , 23 , 24 All participants were informed about the purpose of the study, in accordance with the Declaration of Helsinki, and an ethical approval was granted by the Institutional Review Board (2014-01-173) of IAU. Written consent was taken from all study participants.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Leptin – a major adipokine that regulate the body energy store and inhibit hunger – showed fluctuation during different phases of the menstrual cycle. 7 These variations in energy intake and energy-regulating hormones correspond to changes in ovarian hormones. 8 , 9 The decrease in energy intake may be due to anorexigenic/appetite-suppressing effects of estradiol, 10 , 11 and increased energy intake might be due to orexigenic/appetite stimulatory effects of progesterone.…”
Section: Introductionmentioning
confidence: 99%